2008
DOI: 10.1128/aem.00514-08
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Lactobacillus plantarum 299v Does Not Counteract Unfavorable Phytohemagglutinin-Induced Changes in the Rat Intestinal Microbiota

Abstract: Application of phytohemagglutinin (PHA) in weaning feed has been suggested to stimulate intestinal epithelium maturation. In this study, PHA strongly affected the fecal bacterial population structure of rats. Escherichia coli overgrowth was not prevented by probiotic mannose-adhering Lactobacillus plantarum 299v. Therefore, use of PHA in weaning feed deserves careful evaluation.Plant lectins such as kidney bean-derived phytohemagglutinin (PHA) have gained renewed interest for potential use in animal feed and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…Phytohemagglutinin (PHA) has been shown to induce dysbiosis, accompanied by the hyperproliferation of E. coli , with a key symptom of diarrhea in rats . Pusztai et al reported that PHA promotes epithelial cell turnover, and increases the proportion of immature cells, thereby causing hyperproliferation of E. coli .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytohemagglutinin (PHA) has been shown to induce dysbiosis, accompanied by the hyperproliferation of E. coli , with a key symptom of diarrhea in rats . Pusztai et al reported that PHA promotes epithelial cell turnover, and increases the proportion of immature cells, thereby causing hyperproliferation of E. coli .…”
Section: Introductionmentioning
confidence: 99%
“…Phytohemagglutinin (PHA) has been shown to induce dysbiosis, accompanied by the hyperproliferation of E. coli, 8,9 with a key symptom of diarrhea in rats. 10,11 Pusztai et al 9 reported that PHA promotes epithelial cell turnover, and increases the proportion of immature cells, thereby causing hyperproliferation of E. coli. Furthermore, since PHA is harmless in germ-free animals, 12 small intestine dysfunction and diarrhea induced by PHA are considered to be caused in part by dysbiosis arising from the rapid hyperproliferation of E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…Similar result was found by Oyetayo (2004) that L. acidophilus was able to increase feed consumption and body weight gain of rats infected by enterotoxigenic E. coli (ETEC). Gross et al (2008) also reported that L. plantarum 299v was able to increase feed consumption and body weight gain in diarrhea rats. In addition, L. plantarum 2C12 and L. acidophilus 2B4 isolated from Indonesian meat were also able to improve feed consumption and body weight gain of rats infected by enteropathogenic E. coli (EPEC) (Arief et al, 2010).…”
Section: Body Weight Gain and Feed Consumption Of Ratsmentioning
confidence: 92%
“…Kusumawati et al (2003) reported that L. plantarum BSL was resistant to 5% bile salt and pH 2.5, suggesting that L. plantarum BSL had high survival and ability to adhere to the epithelial cell surface. Gross et al (2008) found that Lactobacillus spp. population in the small intestine of rats treated with L. plantarum 299v was higher (10 6 CFU/g) than control (10 5 CFU/g).…”
Section: Body Weight Gain and Feed Consumption Of Ratsmentioning
confidence: 99%
“…Total BAL isi sekum tikus yang disuplementasi susu Acidophilus mempunyai jumlah populasi yang lebih tinggi sebesar 0,23 log CFU/g dibandingkan kontrol dan 0,56 log CFU/g lebih tinggi dibandingkan dengan total BAL isi sekum tikus yang disuplementasi kefir. Kemampuan BAL strain Lactobacilus achidopilus dalam menghasilkan senyawa adesin manosa pada dinding selnya yang dapat melekat dalam mukosa usus lebih efektif dibandingkan spesies BAL yang berasal dari kefir (Gross et al, 2008) sehingga BAL yang berasal dari susu Acidophilus dapat berkembang dengan baik dan total BAL di dalam usus maupun pada sekum meningkat.…”
Section: Hasil Dan Pembahasanunclassified